The Prophet’s Way of Resolving Divorce - Nurul Hakim; Damirdas Kafa Habibullah (The Indonesian Journal of Islamic Law and Civil Law, 2025)
Divorce is a social phenomenon that has existed for a long time and remains a complex issue in contemporary society. Although marriage is considered a sacred bond that must be maintained in Islam, divorce can be a last resort to maintain the well-being of both parties in certain situations. The Prophet Muhammad provided an example of how to resolve divorce in a fair and humane manner so as not to cause ongoing conflict in society. It is important to understand how the Prophet handled divorce and how it is applied in the Islamic legal system and modern household life. This research is a literature review with a non-interactive qualitative approach or research that leads to exploration, excavation and deepening of related data to answer questions in the formulation of the problem with the object of the study of the hadith on divorce. This study resulted in the first, divorce is recognized in the history of human religion. Among Jews, divorce is not permitted without an excuse. Meanwhile, in responding to divorce, Christians are divided into three groups. First, Catholics prohibit divorce for any reason. Second, the Orthodox sect. And third, the Protestant sect. Both of these sects allow divorce for certain reasons. Second, the hadith on divorce from a socio-historical perspective found that the Prophet had divorced Hafsah and then referred to it again. The Prophet's efforts to refer to Hafsah show that the Prophet remained careful and tried to choose a peaceful path to maintain the marriage as much as possible. Meanwhile, from a psychological perspective, the hadith on divorce can be understood that the hadith has a universal value of benefit for couples to be careful so that they do not get divorced easily.